The Role of Circadian Rhythm Disruptions in Maternal and Fetal Health: A Consideration of Their Potential Effects - Meher, Mantu; Arora, Sweta; Basu, Priyoneel (Disease and Health: Research Developments Vol. 9, 2025)
Circadian rhythms are the natural body clocks that regulate sleep, hormone release, and metabolism. During pregnancy, these rhythms are essential for the well-being of both the mother and the developing baby. However, modern lifestyles, characterized by shift work, excessive exposure to artificial light, and irregular sleep patterns, can disrupt these rhythms. Such disruptions are associated with various complications, including miscarriage, preterm birth, and low birth weight. Additionally, misalignment of circadian rhythms may negatively impact fetal brain development, increasing the risk of mental health issues and learning difficulties later in life. Melatonin, a hormone that helps regulate sleep patterns, can play a protective role in reducing these risks. This review emphasizes the importance of maintaining stable circadian rhythms during pregnancy and suggests that lifestyle changes, along with melatonin therapy, may improve maternal and fetal health outcomes.